Identification, characterization and comparative analysis of pattern recognition receptors (PRR) and nucleotide binding site-leucine rich repeat (NBS-LRR) in Coffea spp. Genome - Santos, Mariana de Lima (2021)
Coffee stands out in world agribusiness, especially in Brazil. However, the production of this commodity has been affected due to the occurrence of several diseases, including rust, whose etiologic agent is the biotrophic fungus Hemileia vastatrix. A promising strategy for disease control is the identification and study of receptors that trigger the signaling for the resistance mechanism in plants. Therefore, the objectives of this work were to identify and characterize pattern recognition receptors (PRRs) in the Coffea arabica genome and analyze the gene expression of these receptors in contrasting cultivars of C. arabica inoculated with H. vastatrix. Besides identifying NLR loci (nucleotide-binding leucine-rich repeat site - NBS-LRR) in C. arabica, C. canephora and C. eugenioides genomes using the NLR-annotator; characterize the distribution of these loci in Coffea spp. and understand the contribution of C. canephora and C. eugenioides to the NLR repertoire of C. arabica. Approaches based on the principle of sequence similarity, motif and domain conservation, phylogenetic analysis, gene expression modulation and ortholog group analysis were used. The results demonstrate that the candidate PRRs in C. arabica (Ca1-LYP, Ca2-LYP, Ca1-CERK1, Ca2-CERK1, Ca-LYK4, Ca1-LYK5 and Ca2-LYK5) have high similarity with the reference PRRs used: Os-CEBiP, At-CERK1, At-LYK4 and At-LYK5. The ectodomains of these receptors showed high identity or similarity with the reference sequences, indicating structural and functional conservation. The candidate PRRs are phylogenetically related to reference PRRs (in Arabidopsis and rice) and those described in other plant species. All candidate receptors had their expression induced after the inoculation with H. vastatrix, since the first time of sampling at 6 hours post-inoculation (hpi). There was a significant increase at 24 hpi for most receptors evaluated and a suppression at 48 hpi. A total of 1311 non-redundant NLR loci were identified in C. arabica, 927 in C. canephora and 1079 in C. eugenioides, of which 809, 562 and 695 are complete loci, respectively. The NLR-annotator showed extremely high sensitivities and specificities (over 99%) for identifying NLR loci in coffee, besides to increasing the detection capability of putative NLRs in the studied genomes. The NLR loci in coffee are distributed among all chromosomes and are organized mostly in clusters. The C. arabica genome present a smaller number of NLR loci when compared to the sum of the parental genomes (C. canephora and C. eugenioides). There are orthologous NLRs (orthogroups) shared between coffee, tomato, potato and reference NLRs and those that are shared only between coffee species. Phylogenetic analysis demonstrated orthologs NLRs shared between C. arabica and the parental genomes and those that were possibly lost. The NLR family members in coffee are subdivided into two main groups: TIR-NLR (TNL) and non-TNL. The Non-TNLs seem to represent an important repertoire of resistance genes in coffee. These results can support functional studies of PRRs and NLRs and contribute to the use of these receptors in the coffee breeding, aiming at the development of resistant cultivars.